A case report of budd-chiari syndrome during puerperium requiring two liver transplants. (7th June 2011) - Anbazhagan, A; Harper, A; Hunter, A; Benson, G; McDougall, N
Abstract : Budd-Chiari syndrome is a rare and serious condition characterised by obstruction to the outflow of hepatic venous blood. Thrombophilias, malignancies, infections and pregnancy have been implicated as causes. Anticoagulation, portacaval shunt placement and orthotopic liver transplant are the treatment options. Here we present the management of a patient who developed Budd-Chiari syndrome during her puerperium and needed two liver transplants. Case report: A 26-year-old para two presented during her third pregnancy to the joint antenatal-haematology clinic. She had a past history of antiphospholipid syndrome, recurrent deep vein thrombosis and pulmonary embolism and was on clexane 80 mg twice a day during pregnancy. At 35 weeks she developed nausea, epigastric pain, chest pain and vasculitis, hence labour was induced and she delivered a baby boy normally. On the second postnatal day she developed severe right upper quadrant pain, hepatosplenomegaly and raised liver function tests. CT and MRI confirmed hepatic vein thrombosis. She developed ascites and recurrent sepsis and received orthotopic liver transplant 3 months after delivery. 2 weeks later she developed hepatic artery thrombosis and hence received repeat transplant. She was discharged 5 months following her delivery. Discussion: Budd-Chiari syndrome during pregnancy has been rarely reported. Our patient developed Budd-Chiari syndrome on the back ground of two prothrombotic events namely pregnancy and antiphospholipid syndrome and needed two orthotopic liver transplants within a span of 3 weeks. There have been no such cases reported in the literature. This case highlights the extreme difficulty in managing these patients.